Monitoreo y evaluación del Hearts, centro de salud Gonzalo Cordero Crespo y Guanujo. febrero-junio 2025 - Duche Cáliz, Andersson Javier (2025)
The overall objective of this study was to evaluate the monitoring and assessment of the HEARTS strategy at the Gonzalo Cordero Crespo and Guanujo Health Centers during the period February-June 2025, as a measure for the prevention and control of high blood pressure in primary care. The research was conducted using a quantitative approach, with a descriptive, cross-sectional, field design. A structured Likert-type questionnaire was administered to health personnel at both centers, addressing key dimensions of the HEARTS strategy such as healthy habits, clinical protocols, access to medications, cardiovascular risk, teamwork, and, especially, monitoring and evaluation systems. The results showed active implementation of the strategy, with an emphasis on clinical records, blood pressure measurement, and health education. Monitoring was perceived as consistent and useful for improving clinical outcomes, although weaknesses were identified in institutional feedback and in the systematic use of data for decision-making. Limitations were also observed in the availability of essential medicines and in the uniform application of clinical tools. Based on these findings, a strengthening proposal was designed, consisting of six operational strategies aimed at improving therapeutic adherence, standardizing care, consolidating teamwork, and optimizing monitoring. It is concluded that, although the HEARTS strategy has been adopted with commitment by health personnel, its impact can be enhanced through structured actions that guarantee sustainability, equity, and quality in cardiovascular care.